2015
DOI: 10.5152/dir.2015.15080
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric thin-section CT: evaluation of pulmonaryinterlobar fissures

Abstract: T he pulmonary interlobar fissures are important landmarks for pulmonary anatomy. They adopt a double membrane structure formed by invagination of the visceral pleura. The interlobar fissures are 1-3 mm thick and consist of the right oblique fissure (ROF), horizontal fissure (HF), and left oblique fissure (LOF) (1, 2). The recognition of pulmonary interlobar fissures and their variations is beneficial for identifying pulmonary lesion locations, evaluating disease progression, selecting surgical operations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Koenigkam-Santos et al 29 described a high agreement between experienced radiologists for the major fissures, but rather moderate for the minor fissure (k=0.53). Cronin et al 31 described a greater than 90% agreement for all fissures, Guan et al 34 found a fair to nearly perfect agreement between two radiologists (k=0.593–0.652) and Koenigkam-Santos et al 28 described a reported interobserver agreement of 0.70–0.76. This is the case with experienced radiologists or pneumologists; inexperienced readers most probably have lower agreement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koenigkam-Santos et al 29 described a high agreement between experienced radiologists for the major fissures, but rather moderate for the minor fissure (k=0.53). Cronin et al 31 described a greater than 90% agreement for all fissures, Guan et al 34 found a fair to nearly perfect agreement between two radiologists (k=0.593–0.652) and Koenigkam-Santos et al 28 described a reported interobserver agreement of 0.70–0.76. This is the case with experienced radiologists or pneumologists; inexperienced readers most probably have lower agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations are the varying patient groups with and without pulmonary disease, different kind of reviewers, various or no criteria to define an incomplete fissure, or used CT-scan technique (eg, slide thickness). 34 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article entitled "Volumetric thin-section CT: evaluation of pulmonary interlobar fissures" by Guan et al (1) in the November-December 2015 issue of Diagnostic and Interventional Radiology. The authors gave detailed information about interlobar fissures, their incompleteness, relationship to vascular structures, CT appearance, and defect location.…”
mentioning
confidence: 99%
“…For assessment on CT, the authors usually state criteria for incomplete fissures, with several using four types accord-ing to the varying presence of vessels, including the situation when a fissure is simply missing. Data from various CT methods were mostly obtained from hundreds of patients 1,[12][13][14][15][16][17][18][19][20][21][22][23] . Only Frija et al 12 used healthy volunteers.…”
Section: Prevalence Of Incomplete Fissuresmentioning
confidence: 99%